1971
DOI: 10.1002/cjce.5450490617
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion effects in catalytic gas oil cracking

Abstract: Wojciechowski's four parameter model of catalyst decay is applied to conversion data for gas oil cracking over a diffusion limited catalyst. The parameters thus obtained are compared with those obtained previously for a diffusion free form of the same catalyst, cracking the same feed stock under identical experimental conditions. The comparison shows that the presence of diffusion affects not only the rate of catalytic cracking but also the rate of aging. It is also shown that the introduction of diffusion phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…The same phenomenon was observed by Best and Wojciechowski [9,16,19]. We report here data for ethyl toluene production for the first time.…”
Section: Discussion Of Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The same phenomenon was observed by Best and Wojciechowski [9,16,19]. We report here data for ethyl toluene production for the first time.…”
Section: Discussion Of Resultssupporting
confidence: 85%
“…This result agrees with the observation of other workers [4,9] who have shown that an REY zeolite calcined at 480°C contains predominantly Bronsted-type active sites.…”
Section: Initial S E L E C T I V I T I E Ssupporting
confidence: 95%
See 2 more Smart Citations
“…In previous publications (Pachovsky, 1971;Best, 1971;Campbell, 1969) it has been proposed that gas oil cracking can be represented by the mechanism A…”
Section: Theorymentioning
confidence: 99%